1997
DOI: 10.1002/(sici)1097-0215(19970917)72:6<1122::aid-ijc30>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Affinity, specificity and T-cell-receptor diversity of melanoma-specific CTL generatedin vitro against a single tyrosinase epitope

Abstract: MHC‐class‐I‐restricted cytotoxic T lymphocytes (CTL) specific for tumor‐associated antigens expressed by malignant cells are important components of the immune response against cancer. Recently, tumor‐specific CTL could be generated in vitro, with responding lymphocytes from the blood of healthy blood donors. In the present study, we confirm that peptide‐specific stimulation in vitro can induce high‐affinity CTL capable of recognizing tumor cells expressing the appropriate tumor antigen. These tyrosinase‐speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This notion is further supported by the crystal structure of a TCR bound to a viral peptide/HLA-A2 complex (40). Although several studies show that conservation of sequence and size of CDR3␤ of CTL is not an absolute determinant of Ag recognition, TCR CDR3 regions do appear to govern peptide fine specificity of CTL (41,42).…”
Section: Discussionmentioning
confidence: 95%
“…This notion is further supported by the crystal structure of a TCR bound to a viral peptide/HLA-A2 complex (40). Although several studies show that conservation of sequence and size of CDR3␤ of CTL is not an absolute determinant of Ag recognition, TCR CDR3 regions do appear to govern peptide fine specificity of CTL (41,42).…”
Section: Discussionmentioning
confidence: 95%
“…As functional data are lacking, no definitive decision can be made whether this combination of highly conserved BVJ gene segment combinations in the context of heterogeneous CDR3 regions within coexisting melanoma sites is indicative of the occurrence of functionally unrelated TCR specificities, which were generated by random mutations in rapidly growing melanoma cells, or, alternatively, results from the recognition of related epitopes of a restricted number of MAA. Support for the latter assumption comes from a manuscript by Visseren et al (1997), who found that in vitro priming of PBL from healthy donors with the tyrosinase 369-377 peptide can induce peptidespecific CTL that, despite a restricted usage of AV and BV gene segments, exhibit a considerable diversity in their CDR3 regions resulting in a distinct lytic fine specificity of each clonotype.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the immune response, particularly T cell‐mediated cytotoxicity, in the anti‐tumour response was demonstrated by the presence of several T cell repertoires with the ability to kill autologous tumours in local tissues 17–20 and by the generation of tumour specific CTL clones from PBMC in human cancer patients. 21,22 We have previously reported that autologous liver cancer‐specific CTL can be induced by stimulation with autologous tumours together with IL‐2 and that these CTL had a potent therapeutic effect on several liver cancer patients. 23 However, all previous clinical trials including ours have demonstrated that the effect of these adoptive immunotherapies was limited.…”
Section: Discussionmentioning
confidence: 99%
“… 23 However, all previous clinical trials including ours have demonstrated that the effect of these adoptive immunotherapies was limited. 17–23 Therefore, the development of more effective tools for adoptive immunotherapy is still urgently required. For this reason, we have attempted to establish a more potent in vitro system to induce autologous tumour‐specific CTL.…”
Section: Discussionmentioning
confidence: 99%